Urban Squats as Eco-Social Resistance to and Resilience in the Face of Capitalist Relations: Case Studies from Barcelona and Rome - Claudio Cattaneo; Salvatore Engel-Di Mauro (Partecipazione e Conflitto, 2015)
This article analyses continuities and discontinuities across time in Italy in the use of direct social actions, defined as forms of action that focus upon directly transforming some specific aspects of society by means of the very action itself, instead of claiming something from the state or other power holders. In doing this, this article offers two main illustrative hypotheses. First, that direct social actions represent a significant part of the repertoire of contention - at least in Italy - and that while they tend to be less visible than protest actions, they should still not be overlooked and treated like something “new” every time they resurface. Second, this article claims that the socio-economic context plays an important role in influencing the extended use of DSAs: if the supply of these forms of action by political actors is constant across time, what changes is the demand, that in times of economic hardship tends to characterise a broader constituency. We conclude by suggesting empirical methods to verify the hypothe-ses proposed, paving the way for future research on this topic.